Feature interactions in telecommunications and software systems VII - Amyot, Daniel, 1970-; Logrippo, L. (Luigi) (IOS Press ; Ohmsha, 2003)
Feature interaction is a phenomenon known to the designers of modern telephone switching systems. This phenomenon occurs when one feature modifies or subverts the operation of another one. This work brings together representatives of the telecommunications industry and the software industry.